The meaning of Environment Design: the uniqueness of the human being in a scenario of transformations (Estudos em Design, 2025)
Design is a field of professional activity that comprises different types of work, such as space planning. This interdisciplinary typology has been evolving, rasing the question of what the role of the Environmental Designer must be in face of contemporary times. The reflection proposed in this article aims to analyze the relevance of the Environmental Design profession for society, demonstrating the transformation processes that led to the construction of a concept of ambiance throughout history. Environmental Psychology is addressed becausethis concept emerged in a social moment of discussions related to human values. This fact might have been the beginning of the transformation of the idea of the environmental object, which brought a systemic view to the relationship between subject and space. As a result, an analysis is presented of how Environmental Design can be configured in face of the current scenario of transformations within a real sense of environmentalismfocusing on the singularity of the human being.